Cooperation and Competition with Hyperscanning Methods: Review and Future Application to Emotion Domain - Balconi, Michela; Vanutelli, Maria E. (Frontiers in Computational Neuroscience, 2017)
Cooperation and competition, as two common and opposite examples of interpersonal dynamics, are thought to be reflected by different cognitive, neural, and behavioral patterns. According to the conventional approach, they have been explored by measuring subjects’ reactions during individual performance or turn-based interactions in artificial settings, that don’t allow on-line, ecological enactment of real-life social exchange. Considering the importance of these factors, and accounting for the complexity of such phenomena, the hyperscanning approach emerged as a multi-subject paradigm since it allows the simultaneous recording of the brain activity from multiple participants interacting. In this view, the present paper aimed at reviewing the most significant work about cooperation and competition by EEG hyperscanning technique, which proved to be a promising tool in capturing the sudden course of social interactions. In detail, the review will consider and group different experimental tasks that have been developed so far: 1) paradigms that used rhythm, music and motor synchronization; 2) card tasks taken from the Game Theory; 3) computerized tasks; 4) and possible real-life applications. Finally, although highlighting the potential contribution of such approach, some important limitations about these paradigms will be elucidated, with a specific focus on the emotional domain.